(untitled) (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted on 20 lactating Kankrej cows divided in four groups according to lactation number one to four and initial stage of lactation with almost same production. Highly significant (P<0.01) difference was observed for let down time in cold-dry season (61.54 s) as compared to hot-humid season (68.13 s), milking time in hot-humid season (245.72 s) as compared to cold-dry season (260.02 s) and milk yield/ milking in cold-dry season (4.300 kg ) as compared to hot-humid season (3.860 kg) while, significant (P<0.05) difference was observed in milk flow rate in cold-dry season (0.990 kg/min) as compared to hot-humid season (0.950 kg/min) .